Epidemiology and risk factors for bronchopulmonary dysplasia in preterm infants born at or less than 32 weeks of gestation - Andrea Sucasas Alonso; Sonia Pértega Diaz; Rebeca Sáez Soto; Alejandro Avila-Alvarez (Elsevier, 2022)
Objectives: To describe risk factors of bronchopulmonary dysplasia in very preterm infants in the first weeks of life. Material and methods: Retrospective cohort study of preterm infants ≤ 32 weeks of gestational age and birth weight ≤ 1500 g. A multivariate logistic regression analysis was performed to identify independent risk factors for bronchopulmonary dysplasia in the first weeks of life. Results: A total of 202 newborns were included in the study (mean gestational age 29.5 ± 2.1 weeks), 61.4% never received invasive mechanical ventilation. The incidence of bronchopulmonary dysplasia was 28.7%, and 10.4% of the patients were diagnosed with moderate-severe bronchopulmonary dysplasia. Bronchopulmonary dysplasia was independently associated with gestational age (P < 0.001; OR = 0.44 (95% CI = 0.30-0.65)), the need for mechanical ventilation on the first day of life (P = 0.001; OR = 8.13 ((95% CI = 2.41-27.42)), nosocomial sepsis (P < 0.001; OR = 9.51 ((95% CI = 2.99-30.28)) and FiO2 on day 14 (P < 0.001; OR = 1.39 ((95% CI = 1.16-1.66)). Receiving mechanical ventilation at the first day of life (P = 0.008; OR = 5.39 ((95% CI = 1.54-18.89)) and at the third day of life (P = 0.001; OR = 9.99 ((95% CI = 2.47-40.44)) and nosocomial sepsis (P = 0.001; OR = 9.87 ((95% CI = 2.58-37.80)) were independent risk factors for moderate-severe bronchopulmonary dysplasia. Conclusions: Gestational age, mechanical ventilation in the first days of life and nosocomial sepsis are early risk factors for bronchopulmonary dysplasia. The analysis of simple and objective clinical data, allows us to select a group of patients at high risk of bronchopulmonary dysplasia in whom it could be justified to act more aggressively, and shows areas for improvement to prevent its development or reduce its severity. Resumen: Objetivos: Describir los factores de riesgo de displasia broncopulmonar en las primeras semanas de vida en recién nacidos muy prematuros. Material y métodos: Estudio observacional de cohortes retrospectivo en recién nacidos ≤32 semanas y ≤ 1500 gramos. Se realizó un análisis multivariante de regresión logística para identificar factores de riesgo independientes en las primeras semanas de vida. Resultados: Se incluyeron 202 recién nacidos con una edad gestacional media de 29,5 ± 2,1 semanas. El 61,4% de los pacientes no recibió ventilación mecánica invasiva. El 28,7% fue diagnosticado de displasia broncopulmonar, y el 10,4% de displasia broncopulmonar moderada-grave. La edad gestacional (p < 0,001; OR = 0,44 (95%IC = 0,30-0,65)), la ventilación mecánica en el día 1 (p = 0,001; OR = 8,13 ((95%IC = 2,41-27,42)), la sepsis nosocomial (p < 0,001; OR = 9,51 ((95%IC = 2,99-30,28)) y la FiO2 en el día 14 (p < 0,001; OR = 1,39 ((95%IC = 1,16-1,66)) fueron los factores de riesgo independientes de displasia broncopulmonar. La ventilación mecánica el día 1 (p = 0,008; OR = 5,39 ((95%IC = 1,54-18,89)) y 3 de vida (p = 0,001; OR = 9,99 ((95%IC = 2,47-40,44)) y la sepsis nosocomial (p = 0,001; OR = 9,87 ((95%IC = 2,58-37,80)) se asociaron al desarrollo de displasia broncopulmonar moderada-grave. Conclusiones: La edad gestacional, la ventilación mecánica en los primeros días de vida y la sepsis nosocomial son factores de riesgo precoces de displasia broncopulmonar. El análisis de datos clínicos sencillos y objetivos nos permite seleccionar a un grupo de pacientes con alto riesgo de desarrollar displasia broncopulmonar en el que podría estar justificado actuar de forma más agresiva, y nos muestra áreas de mejora para prevenir su desarrollo o disminuir su gravedad.